Active Surveillance Versus Immediate Surgery in Clinically Complete Responders After Neoadjuvant Chemoradiotherapy for Esophageal Cancer: A Multicenter Propensity Matched Study. Issue 6 (4th December 2021) - van der Wilk, Berend J.; Noordman, Bo J.; Neijenhuis, Lisanne K. A.; Nieboer, Daan; Nieuwenhuijzen, Grard A. P.; Sosef, Meindert N.; van Berge Henegouwen, Mark I.; Lagarde, Sjoerd M.; Spaander, Manon C. W.; Valkema, Roelf; Biermann, Katharina; Wijnhoven, Bas P. L.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: This study compared outcomes of patients with esophageal cancer and clinically complete response (cCR) after neoadjuvant chemoradiotherapy (nCRT) undergoing active surveillance or immediate surgery. Background: Since nearly one-third of patients with esophageal cancer show pathologically complete response after nCRT according to CROSS regimen, the oncological benefit of immediate surgery in cCR is topic of debate. Methods: Patients with cCR based on endoscopic biopsies and endoscopic ultrasonography with fine-needle aspiration initially declining or accepting immediate surgery after nCRT were identified between 2011 and 2018. Primary endpoint was overall survival (OS). The secondary endpoints were progression-free survival (PFS), rate and timing of distant dissemination, and postoperative outcomes. Results: Some 98 patients with cCR were identified: 31 in the active surveillance- and 67 in the immediate surgery group with median followup of survivors of 27.7 and 34.8 months, respectively. Propensity score matching resulted in 2 comparable groups (n = 29 in both groups). Patients undergoing active surveillance or immediate surgery had a 3-year OS of 77% and 55% (HR 0.41; 95% CI 0.14–1.20, P = 0.104), respectively. The 3-year PFS was 60% and 54% (HR 1.08; 95% CI 0.44–2.67, P = 0.871), respectively. Patients undergoing active surveillance or immediate surgery had a comparable distant dissemination rate (both groups 28%), radical resection rate (both groups 100%), and severity of postoperative complications (Clav- ien-Dindo grade ≥ 3: 43% vs 45%, respectively). Conclusion: In this retrospective study, OS and PFS in patients with cCR undergoing active surveillance or immediate surgery were not significantly different. Active surveillance with postponed surgery for recurrent disease was not associated with a higher distant dissemination rate or more severe adverse postoperative outcomes.